Conscious money living, creating, and investing with your values for a sustainable new prosperity - Aburdene, Patricia (New York Atria Paperback Hillsboro, Or Beyond Words, 2012)
"In Conscious Money Patricia Aburdene, co-Author of Megatrends 2000, shows readers how to grow wealth by honoring and integrating their values and the world of prosperity thinking with sound money sense. She offers practical strategies to penetrate paralyzing fear in the face of stalled real estate sales, a volatile stock market, and the continued threat of job loss--as well as concrete advice to navigate a radically different economy as the recovery gains traction and new opportunities blossom. Conscious Money aims to shift financial thinking from dread to opportunity. Each chapter describes a New Rule of Conscious Money. Each New Rule is your gateway to abundance, fulfillment and sound financial practice. 1. Enjoy spending by focusing on products/services that embody your values. 2. For best results, merge abundance thinking with sensible finance. 3. Self-mastery is your greatest financial asset. 4. Personal consciousness determines financial abundance. 5. Expand your horizons: Conscious Money is global. 6. Invest only in companies as conscious as you are. 7. Welcome to the New Economy of Consciousness, where new wealth (and new jobs) primarily depend on the genius of human creativity. Conscious Money is a megatrend, a grassroots movement of investors and consumers, and a business model that's up and running in hundreds of famous firms like Google, Honda, and Costco. While the traditional model favors investors, Conscious Money honors investors, customers, employees, suppliers, communities, and the planet"--
"Patricia Aburdene, author of the bestselling Megatrends 2010, brings together the spiritual and practical in a guide to achieving prosperity through the values-based megatrend of Conscious Capitalism. In Conscious Money, Patricia Aburdene shows readers how to grow wealth by honoring and integrating their values with sound money sense. She offers practical strategies to penetrate paralyzing fear in the face of stalled real estate sales, a volatile stock market, and the threat of job loss--and gives concrete advice on how to navigate a radically different economy as the recovery gains traction and new opportunities blossom. Conscious Money aims to shift financial thinking from dread to empowerment. Conscious Money is a megatrend, a grass roots movement that promotes a holistic and values based approach to money. While the traditional model favors investors only, Conscious Money is centered on honoring personal values, customers, employees, suppliers, communities, and the environment as well. Readers learn how to define their personal money values, close the gap between spiritual thinking and money, and listen to their intuition, while simultaneously acting with sound money management principles"--
Includes bibliographical references (p. 263-296)
1
Keywords: BODY, MIND & SPIRIT / General; BUSINESS & ECONOMICS / Personal Finance / Money Management; Finance, Personal -- Psychological aspects; HOUSE & HOME / Sustainable Living; Investments -- Psychological aspects